Study on the Light Stability of Poly(p-phenylenebenzobisoxazole) Fiber - Wu, Junling; Zhuang, Qixin; Liu, Xiaoyun; Qian, Jun; Han, Zhewen (Asian Journal of Chemistry, 2014)
Although poly(p-phenylenebenzobisoxazole) (PBO) fiber has outstanding mechanical performances and thermal stability but its application was hindered seriously due to low light stability. Thus, main aim in present work is to increase the light stability of PBO fiber. Four means, such as reacted sol-gel means, mixed sol-gel means, silane sol-gel means and physical adhesion means, were performed for light stabilizers to adhere on the surface of PBO fiber. The experimental results indicate that the PBO fibers processed by reacted sol-gel means exhibit flat surface without obvious particle accumulation. Contrasted with those fibers processed by other three means, these fibers show better light stability. After 130 h of light irradiation, the mechanical tensile strength of the fibers processed by reacted sol-gel means is still over 75 % of strength of unaged fiber and the strength is much higher than the aged original fibers whose strength is ca. 40 % of that of unaged original fiber.